High-transparency nanofiber membrane and method for manufacturing the same
Patent Information
- Application Number
- CN202311656101.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-05
AI Technical Summary
特别是在个人防护领域,由薄膜材料组成的口罩已成为最重要、使用最普遍的个人防护工具,与此同时,随着网络科技的迅猛发展,人们的日常生活和出行都离不开人脸识别系统,如网上购物和消费、机场和火车站等公共场所的身份验证,但现有口罩的透光性极差,口罩佩戴者无法成功进行身份验证,当进行人脸识别时必须要摘下口罩,这也会造成病毒感染概率的增加,不利于自身防护
1、由于本申请的方法,采用纳米纤维素和丝素蛋白混合浇筑成膜,在浇筑时,在模具内放置PET正六边形纱网,使得纤维膜有序排列,形成纳米纤维素/丝素蛋白复合膜,然后在其表面静电纺丝,形成PLA纳米纤维膜,由此制成透明度高、孔隙率高,透气性好和过滤效果好的纳米纤维膜。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials technology, and more specifically, to a high-transparency nanofiber membrane and its preparation method. Background Technology
[0002] In recent years, transparent thin-film materials have attracted increasing attention from researchers. Due to their excellent optical properties, transparent thin-film materials are widely used in optoelectronic devices, biomedicine, environmental engineering, and personal protective equipment. Especially in the field of personal protective equipment, masks made of thin-film materials have become the most important and widely used personal protective tool. Meanwhile, with the rapid development of network technology, people's daily lives and travel are inseparable from facial recognition systems, such as online shopping and consumption, and identity verification in public places like airports and train stations. However, existing masks have extremely poor light transmittance, making it impossible for mask wearers to successfully verify their identity. When undergoing facial recognition, masks must be removed, which increases the probability of viral infection and is detrimental to personal protection. Although existing masks have high protective performance, their poor breathability and light transmittance have seriously affected the comfort and health of frontline medical workers who need to wear multiple layers of masks for extended periods, as well as communication between medical workers and patients.
[0003] Fiber membranes are thin film materials with a fiber network structure, possessing excellent flexibility, high porosity, and a large specific surface area. However, their surface light reflection and internal light scattering are severe, making it difficult to achieve high light transmittance. Common methods for achieving high transparency in fiber membranes include mechanical pressure, hot pressing, and polymer filling. However, the high filling pressure damages the fiber morphology and spatial structure of the fiber membrane, resulting in lower porosity and reduced air permeability.
[0004] Regarding the aforementioned technologies, the inventors have discovered that developing nanofiber membranes with high light transmittance, good air permeability, and filtration properties is an urgent problem to be solved. Summary of the Invention
[0005] In order to make the nanofiber membrane have high light transmittance, good air permeability and filtration performance, this application provides a high transparency nanofiber membrane and its preparation method.
[0006] In a first aspect, this application provides a method for preparing a high-transparency nanofiber membrane, employing the following technical solution: A method for preparing a high-transparency nanofiber membrane includes the following steps: Nanocellulose and silk fibroin were mixed in a mass ratio of 4-6:4-6 and dissolved in a eutectic solvent to obtain a mixed solution with a concentration of 8-12 wt%. A PET hexagonal mesh is placed in a mold, the mixed solution is added to the mold, the film is poured and dried to obtain a semi-finished product, which is then soaked in a coagulation bath, peeled off, and air-dried to obtain a nanocellulose / silk fibroin composite film. Polylactic acid is dissolved to prepare a PLA solution with a concentration of 7-10 wt%. Using the nanocellulose / silk fibroin composite membrane as the receiving substrate, electrospinning is performed to form a PLA nanofiber membrane on the nanocellulose / silk fibroin composite membrane, thereby producing a highly transparent nanofiber membrane.
[0007] By adopting the above technical solution, silk fibroin, an important natural polymer material, is mainly composed of two chain-like polypeptides linked by disulfide bonds. However, silk fibroin itself is difficult to form a gel. Therefore, another natural polymer material, cellulose, is introduced as a supporting framework. Cellulose contains a large number of hydroxyl groups and easily forms a gel. There are strong intermolecular forces between the two, resulting in good compatibility and the acquisition of membrane materials with excellent mechanical strength and transparency.
[0008] The internal structures of silk fibroin and cellulose are very complex, and they have strong hydrogen bond interactions. Eutectic solvents are a new type of liquid with strong hydrogen bond binding ability and strong dissolving ability. Effective ions that can dissolve silk fibroin and cellulose are introduced into the solvent, which further breaks the hydrogen bond interactions in cellulose and silk fibroin, thereby achieving the purpose of dissolution.
[0009] Using a PET hexagonal mesh as a framework, a composite film was prepared by casting and fabricating silk fibroin fibers and nanocellulose fibers. The silk fibroin fibers and nanocellulose fibers exhibited an interlocking mesh structure with a relatively smooth surface and high light transmittance. When the mixed solution is cast into a film on a PET hexagonal mesh, the PET hexagonal mesh serves as the framework structure, with more fibers deposited on the framework. The channel structure, however, has a smaller fiber deposit. In both structures, the fibers are arranged at concentrated angles, exhibiting a high degree of order. This ordered fiber arrangement reduces light propagation resistance and light loss, facilitating the transmission of visible light. When light propagates within the composite film, the channel structure, with its smaller thickness and ordered fiber arrangement, experiences lower propagation resistance and absorption loss. The framework structure, with its larger fiber deposit and thickness, suffers from higher light absorption loss than the channel structure, but its smaller area means light preferentially passes through the channel structure, making it the primary light propagation channel. Achieving high visible light transmission and exhibiting excellent optical transparency; the orderly arrangement of fibers on the PET hexagonal mesh maintains high porosity, improving air permeability and filtration, and the PET hexagonal mesh provides a certain deformation capacity, giving the composite membrane excellent flexibility and self-support, making it less prone to brittle fracture; polylactic acid, as a biodegradable polymer material, has good gloss and transparency. Using the nanocellulose / silk fibroin composite membrane as the receiving substrate, PLA nanofiber membranes are obtained on the nanocellulose / silk fibroin composite membrane as the receiving substrate through electrospinning, thus obtaining a highly transparent nanofiber membrane composed of the nanocellulose / silk fibroin composite membrane as the receiving substrate and the PLA nanofiber membrane.
[0010] Preferably, the PLA solution also contains bacterial cellulose, and the mass ratio of bacterial cellulose to polylactic acid in the PLA solution is 0.3-0.45:1.
[0011] While polylactic acid (PLA) exhibits high gloss and transparency through the aforementioned technical solutions, its slow crystallization rate and poor toughness can negatively impact the tensile strength of nanofiber membranes. Therefore, a certain amount of bacterial cellulose is added to the PLA solution. Bacterial cellulose, synthesized by microorganisms, is a chain-like polymer composed of pyranose residues and β-1,4-glycosidic bonds, exhibiting a unique three-dimensional network structure with high specific surface energy. It can adsorb small particulate pollutants from the air and, as a heterogeneous nucleating agent, can increase the crystallization rate of PLA, improve the toughness of PLA nanofiber membranes, and reduce brittleness. However, if the amount of bacterial cellulose is too high, the high porosity will lead to a decrease in the transparency of the PLA nanofiber membrane.
[0012] Preferably, the bacterial cellulose undergoes the following pretreatment: Bacterial cellulose, L-lactide and stannous octoate were mixed, and dimethyl sulfoxide was added. The mixture was reacted at 130-140℃ for 9-10 hours to obtain bacterial cellulose grafts. Add whey protein concentrate to a 78-80 wt% acetic acid solution and stir at 75-80℃ to form a 1-1.5 wt% solution. Add bacterial cellulose graft, mix and stir, and then dry.
[0013] By employing the above technical solution, because bacterial cellulose exhibits strong hydrophilicity and its interfacial compatibility with polylactic acid (PLA) needs improvement, bacterial cellulose is treated with L-lactide. Dimethyl sulfoxide (DMSO) is used as a solvent in the bacterial cellulose treatment. DMSO can disrupt some of the hydrogen bonds between bacterial cellulose molecules, allowing lactide molecules to easily penetrate the interior of the bacterial cellulose filaments and better contact the hydroxyl groups on the surface of the bacterial cellulose filaments. This results in a more compact arrangement of the bacterial cellulose filaments, reducing their porosity and preventing strong light scattering caused by the pores of the bacterial cellulose, which would otherwise reduce the transparency of the PLA nanofiber membrane. Furthermore, L-lactide undergoes a ring-opening reaction on bacterial cellulose to form PLA, which improves the interfacial compatibility between bacterial cellulose and polylactic acid, thereby enhancing the mechanical strength of the PLA nanofiber membrane. Whey protein concentrate, after treatment with acetic acid solution, carries a large amount of positive charge in an acidic environment. Due to the repulsive force of like charges within the protein molecules, the helical structure of the protein tends to be unstable, with some helical structures transforming into more open folded structures or uncoiled structures. This more open protein structure exposes a large number of functional groups, increasing the contact opportunities and contact area between functional groups and pollutant particles, thus improving filtration efficiency.
[0014] Preferably, the mass ratio of the whey protein concentrate to the bacterial cellulose graft is 0.5-1:2.
[0015] By adopting the above technical solution, if the whey protein concentrate is too much, it will easily cause a decrease in the transparency of the PLA nanofiber membrane; if the whey protein concentrate is too little, the filtration effect on pollutants will be poor.
[0016] Preferably, the nanocellulose / silk fibroin composite membrane undergoes the following pretreatment: The nanocellulose / silk fibroin composite membrane is immersed in a 15-17% sodium hydroxide aqueous solution and allowed to stand for 10-12 hours. After washing with distilled water until neutral, it is dried and then immersed in an impregnation solution containing isopropanol, a 3.5-4 wt% sodium hydroxide aqueous solution, and a 45-50 wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution. The membrane is then soaked at 40-45℃ for 3-4 hours, washed with water, and dried.
[0017] By adopting the above technical solution, after alkaline treatment, the nanocellulose / silk fibroin composite membrane forms a scale-like and spike-like nano-rough structure on its surface, significantly improving the surface roughness of the fiber. This rough structure can significantly improve air filtration performance, and its extraction can effectively reduce air resistance during the filtration process, thereby enhancing filtration performance. Then, the nanocellulose / silk fibroin composite membrane is treated with quaternary ammonium cationic 3-chloro-2-hydroxypropyltrimethylammonium chloride. 3-chloro-2-hydroxypropyltrimethylammonium chloride carries a positive charge and has a Coulombic force with negatively charged microorganisms, effectively adsorbing microorganisms. Moreover, due to the reduced crystallinity, the specific surface area of 3-chloro-2-hydroxypropyltrimethylammonium chloride increases, improving the filtration effect on small particulate pollutants.
[0018] Preferably, the side length of the regular hexagon in the PET hexagonal mesh is 1.5-2mm.
[0019] By adopting the above technical solution, the PET hexagonal mesh with the above side length serves as the main body to bear external forces in the nanocellulose / silk fibroin composite film, providing mechanical support for improving the nanocellulose / silk fibroin composite film and improving its tensile strength.
[0020] Preferably, the thickness ratio of the nanocellulose / silk fibroin composite membrane to the PLA nanofiber membrane is 1:10-20.
[0021] By adopting the above technical solution, the thickness ratio enables the nanofiber membrane to have good air permeability and filtration effect, while also having high transparency.
[0022] Preferably, the eutectic solvent is a 5-8 wt% solution of 1,5-diazabicyclo[4.3.0]non-5-ene in acetylacetic acid.
[0023] By adopting the above technical solution, the solvent system can not only dissolve cellulose and silk fibroin simultaneously and rapidly, but also maintain the integrity of the polymer structure and is easy to recycle.
[0024] Preferably, the coagulation bath is a 73-75 wt% aqueous ethanol solution.
[0025] By adopting the above technical solution, the ethanol solution has a better coagulation effect and can quickly solidify the semi-finished product into a film.
[0026] Secondly, this application provides a high-transparency nanofiber membrane, employing the following technical solution: A high-transparency nanofiber membrane is prepared using a high-transparency nanofiber membrane preparation method employing the above-mentioned technical solution.
[0027] In summary, this application has the following beneficial effects: 1. The method of this application uses a mixture of nanocellulose and silk fibroin to cast a film. During casting, a PET hexagonal mesh is placed in the mold so that the fiber membrane is arranged in an orderly manner to form a nanocellulose / silk fibroin composite membrane. Then, electrospinning is performed on its surface to form a PLA nanofiber membrane, thereby producing a nanofiber membrane with high transparency, high porosity, good air permeability and good filtration effect.
[0028] 2. In this application, bacterial cellulose is preferably added to the PLA solution to improve the porosity of the PLA nanofiber membrane, enhance the filtration effect, reduce the pressure difference during filtration, and improve the air permeability. L-lactide is used to carry out a ring-opening reaction on the bacterial cellulose to improve the compatibility between bacterial cellulose and polylactic acid, reduce the porosity of bacterial cellulose, reduce the scattering of light by the bacterial cellulose pores, and reduce the impact of bacterial cellulose addition on the transparency of the PLA nanofiber membrane. In addition, whey protein concentrate is used for treatment, thereby further improving the filtration effect of the nanofiber membrane.
[0029] 3. In this application, alkaline solution is preferably used to treat the nanocellulose / silk fibroin composite membrane to produce a nano-rough structure. Then, the nanocellulose / silk fibroin composite membrane is impregnated with quaternary ammonium salt-type cationic 3-chloro-2-hydroxypropyltrimethylammonium chloride to improve the filtration effect of the nanocellulose / silk fibroin composite membrane. Detailed Implementation
[0030] The following embodiments provide a further detailed description of this application.
[0031] Example 1: Preparation of bacterial cellulose: 1 wt% glucose, 1 wt% yeast extract, 4 wt% ethanol, 5% bromocresol purple ethanol solution (0.04% by volume), and 2 wt% agar were mixed and sterilized at 121°C for 20 min at the natural pH. After sterilization, when the temperature dropped to 50°C, ethanol was added to prepare a liquid culture medium. *Acetobacter xyloside* was inoculated and cultured at 30°C and 50% humidity for one week. At this time, a BC membrane of a certain thickness grew at the gas-liquid interface. The membrane was treated with sodium hydroxide and distilled water to make the pH 7. The BC membrane was then frozen with liquid nitrogen, freeze-dried, ultracentrifuged and ground, and sieved through a standard sieve with a pore size of 0.45 mm to obtain bacterial cellulose powder. Example
[0032] In the following examples, nanocellulose and silk fibroin were selected from Shaanxi Yunsen Biotechnology, model number 341; polylactic acid model number 4032D; bacterial cellulose was prepared from bacterial cellulose in Example 1; L-lactide was selected from Wuhan Haishan Technology; and whey protein concentrate with a concentration of 80% was selected from Shanghai Yuanye Biotechnology.
[0033] Example 1: A method for preparing a high-transparency nanofiber membrane, comprising the following steps: S1. Mix 50g of nanocellulose and silk fibroin at a mass ratio of 5:5, dissolve in a eutectic solvent to obtain a mixed solution with a concentration of 10wt%. The eutectic solvent is a 5wt% solution of 1,5-diaza-hybridized bicyclo[4.3.0]-5-nonene in acetylpropionic acid. S2. Place a PET hexagonal mesh with a side length of 1.5 mm into a mold, add the mixed solution into the mold, pour it into a film, dry it at 25°C to obtain a semi-finished product, soak it in a coagulation bath, peel it off, and air dry it naturally to obtain a nanocellulose / silk fibroin composite film with a thickness of 15 μm. The coagulation bath is an anhydrous ethanol solution with a concentration of 73 wt%. S3. Dissolve 100g of polylactic acid in dichloromethane to prepare a PLA solution with a concentration of 10wt%. Use the nanocellulose / silk fibroin composite membrane as the receiving substrate, electrospin, and vacuum dry at 50℃ for 24h to form a PLA nanofiber membrane on the nanocellulose / silk fibroin composite membrane, thereby producing a highly transparent nanofiber membrane. The thickness ratio of PLA nanofibers to nanocellulose / silk fibroin composite membrane is 10:1. During electrospinning, the spinning voltage is 18kV, the distance between the syringe and the receiving substrate is 15cm, and the syringe advance speed is 0.15ml / h.
[0034] Example 2: A method for preparing a high-transparency nanofiber membrane, comprising the following steps: S1. Mix 50g of nanocellulose and silk fibroin at a mass ratio of 5:5, dissolve in a eutectic solvent to obtain a mixed solution with a concentration of 10wt%. The eutectic solvent is an acetylated propionic acid solution of 1,5-diaza-hybridized bicyclo[4.3.0]-5-nonene with a concentration of 8wt%. S2. Place a PET hexagonal mesh with a side length of 2mm into a mold, add the mixed solution into the mold, cast into a film, dry at 25°C to obtain a semi-finished product, soak in a coagulation bath, peel off, and air dry naturally to obtain a nanocellulose / silk fibroin composite film with a thickness of 10μm. The coagulation bath is an anhydrous ethanol solution with a concentration of 75wt%. S3. Dissolve 100g of polylactic acid in dichloromethane to prepare a PLA solution with a concentration of 8wt%. Use the nanocellulose / silk fibroin composite membrane as the receiving substrate, electrospin, and vacuum dry at 50℃ for 24h to form a PLA nanofiber membrane on the nanocellulose / silk fibroin composite membrane, thereby producing a highly transparent nanofiber membrane. The thickness ratio of PLA nanofibers to nanocellulose / silk fibroin composite membrane is 20:1. During electrospinning, the spinning voltage is 18kV, the distance between the syringe and the receiving substrate is 15cm, and the syringe advance speed is 0.15ml / h.
[0035] Example 3: A method for preparing a high-transparency nanofiber membrane, comprising the following steps: S1. Mix 50g of nanocellulose and silk fibroin at a mass ratio of 5:5, dissolve in a eutectic solvent to obtain a mixed solution with a concentration of 10wt%. The eutectic solvent is a 6.5wt% solution of 1,5-diaza-hybridized bicyclo[4.3.0]-5-nonene in acetylpropionic acid. S2. Place a PET hexagonal mesh with a side length of 2mm into a mold, add the mixed solution into the mold, cast into a film, dry at 25°C to obtain a semi-finished product, soak in a coagulation bath, peel off, and air dry naturally to obtain a nanocellulose / silk fibroin composite film with a thickness of 20μm. The coagulation bath is an anhydrous ethanol solution with a concentration of 75wt%. S3. Dissolve 100g of polylactic acid in dichloromethane to prepare a PLA solution with a concentration of 7wt%. Use the nanocellulose / silk fibroin composite membrane as the receiving substrate, electrospin, and vacuum dry at 50℃ for 24h to form a PLA nanofiber membrane on the nanocellulose / silk fibroin composite membrane, thereby producing a highly transparent nanofiber membrane. The thickness ratio of PLA nanofibers to nanocellulose / silk fibroin composite membrane is 15:1. During electrospinning, the spinning voltage is 18kV, the distance between the syringe and the receiving substrate is 15cm, and the syringe advance speed is 0.15ml / h.
[0036] Example 4: A method for preparing a high-transparency nanofiber membrane, the difference from Example 1 is that in step S1, the mass ratio of nanocellulose and silk fibroin is 4:6.
[0037] Example 5: A method for preparing a high-transparency nanofiber membrane, which differs from Example 1 in that, in step S1, the mass ratio of nanocellulose to silk fibroin is 6:4.
[0038] Example 6: A method for preparing a high-transparency nanofiber membrane, which differs from Example 1 in that, in step S3, 45g of bacterial cellulose is added to the PLA solution, and the mass ratio of bacterial cellulose to polylactic acid is 0.45:1.
[0039] Example 7: A method for preparing a high-transparency nanofiber membrane, which differs from Example 1 in that, in step S3, 30g of bacterial cellulose is added to the PLA solution, and the mass ratio of bacterial cellulose to polylactic acid is 0.3:1.
[0040] Example 8: A method for preparing a high-transparency nanofiber membrane, which differs from Example 6 in that the mass ratio of bacterial cellulose to polylactic acid is 0.1:1.
[0041] Example 9: A method for preparing a high-transparency nanofiber membrane, which differs from Example 6 in that the mass ratio of bacterial cellulose to polylactic acid is 0.6:1.
[0042] Example 10: A method for preparing a high-transparency nanofiber membrane, differing from Example 6 in that the bacterial cellulose undergoes the following pretreatment: 6.5g of bacterial cellulose, L-lactide and stannous octoate were mixed and 6000g of dimethyl sulfoxide were added. The mixture was stirred evenly and reacted at 80℃ for 1h. Then the temperature was raised to 140℃ and stirred for 9h to obtain bacterial cellulose graft. The mass ratio of bacterial cellulose to L-lactide was 2:85 and the molar ratio of stannous octoate to L-lactide was 1:500. Whey protein concentrate was added to an 80 wt% acetic acid solution and stirred at 80°C to form a 1.5 wt% solution. Bacterial cellulose graft was then added, mixed, stirred, and dried. The mass ratio of whey protein concentrate to bacterial cellulose graft was 1:2.
[0043] Example 11: A method for preparing a high-transparency nanofiber membrane, differing from Example 6 in that the bacterial cellulose undergoes the following pretreatment: 6.5g of bacterial cellulose, L-lactide and stannous octoate were mixed and 6000g of dimethyl sulfoxide were added. The mixture was stirred evenly and reacted at 80℃ for 1h. Then the temperature was raised to 130℃ and stirred for 10h to obtain bacterial cellulose graft. The mass ratio of bacterial cellulose to L-lactide was 2:85 and the molar ratio of stannous octoate to L-lactide was 1:500. Whey protein concentrate was added to a 78 wt% acetic acid solution and stirred at 75°C to form a 1.0 wt% solution. Bacterial cellulose graft was then added, mixed, stirred, and dried. The mass ratio of whey protein concentrate to bacterial cellulose graft was 0.5:2.
[0044] Example 12: A method for preparing a high-transparency nanofiber membrane, differing from Example 10 in that the bacterial cellulose undergoes the following pretreatment: Whey protein concentrate was added to an 80wt% acetic acid solution and stirred at 80℃ to form a 1.5wt% solution. 6.5g of bacterial cellulose was added, mixed and stirred, and then dried. The mass ratio of whey protein concentrate to bacterial cellulose was 1:2.
[0045] Example 13: A method for preparing a high-transparency nanofiber membrane, differing from Example 10 in that the bacterial cellulose undergoes the following pretreatment: 6.5g of bacterial cellulose, L-lactide, and stannous octoate were mixed and 6000g of dimethyl sulfoxide were added. The mixture was stirred until homogeneous and reacted at 80℃ for 1 hour. The temperature was then raised to 140℃ and stirred for 9 hours to obtain the bacterial cellulose graft. The mass ratio of bacterial cellulose to L-lactide was 2:85, and the molar ratio of stannous octoate to L-lactide was 1:500.
[0046] Example 14: A method for preparing a high-transparency nanofiber membrane, the difference from Example 10 is that the mass ratio of whey protein concentrate to bacterial cellulose graft is 0.1:2.
[0047] Example 15: A method for preparing a high-transparency nanofiber membrane, which differs from Example 10 in that the mass ratio of whey protein concentrate to bacterial cellulose graft is 1.5:2.
[0048] Example 16: A method for preparing a high-transparency nanofiber membrane, differing from Example 10 in that the nanocellulose / silk fibroin composite membrane undergoes the following pretreatment: The nanocellulose / silk fibroin composite membrane was immersed in a 17% sodium hydroxide aqueous solution and allowed to stand for 12 hours. After washing with distilled water until neutral, it was dried at 30°C. Then, it was immersed in an impregnation solution containing 600 ml of isopropanol, 120 ml of a 4 wt% sodium hydroxide aqueous solution, and 45 ml of a 50 wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution and soaked at 45°C for 3 hours. After washing twice with water, it was dried at 45°C.
[0049] Example 17: A method for preparing a high-transparency nanofiber membrane, differing from Example 10 in that the nanocellulose / silk fibroin composite membrane undergoes the following pretreatment: The nanocellulose / silk fibroin composite membrane was immersed in a 15% sodium hydroxide aqueous solution and allowed to stand for 10 hours. After washing with distilled water until neutral, it was dried at 30°C. Then, it was immersed in an impregnation solution containing 600 ml of isopropanol, 120 ml of a 3.5 wt% sodium hydroxide aqueous solution, and 45 ml of a 45 wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution. It was soaked at 40°C for 4 hours, washed twice with water, and dried at 45°C.
[0050] Example 18: A method for preparing a high-transparency nanofiber membrane, the difference from Example 14 is that the nanocellulose / silk fibroin composite membrane is not soaked in sodium hydroxide aqueous solution.
[0051] Comparative Example Comparative Example 1: A method for preparing a high-transparency nanofiber membrane, which differs from Example 1 in that, in step S1, the mass ratio of nanocellulose to silk fibroin is 2:8.
[0052] Comparative Example 2: A method for preparing a high-transparency nanofiber membrane, which differs from Example 1 in that, in step S1, the mass ratio of nanocellulose to silk fibroin is 8:2.
[0053] Comparative Example 3: A method for preparing a high-transparency nanofiber membrane, which differs from Example 1 in that, in step S1, the mass ratio of nanocellulose and silk fibroin is 5:5, but the concentration of the mixed solution is 20%.
[0054] Comparative Example 4: A method for preparing a high-transparency nanofiber membrane, which differs from Example 1 in that, in step S2, a PET hexagonal mesh is not placed in the mold, and the mixed solution is directly poured into the mold.
[0055] Comparative Example 5: A method for preparing a high-transparency nanofiber membrane, comprising the following steps: S1. Mix 50g of nanocellulose and silk fibroin at a mass ratio of 5:5, dissolve in a eutectic solvent to obtain a mixed solution with a concentration of 10wt%. The eutectic solvent is a 5wt% solution of 1,5-diaza-hybridized bicyclo[4.3.0]-5-nonene in acetylpropionic acid. S2. Place a PET hexagonal mesh with a side length of 1.5 mm into a mold, add the mixed solution into the mold, cast into a film, dry at 25°C to obtain a semi-finished product, soak in a coagulation bath, peel off, and air dry naturally to obtain a nanofiber membrane with a thickness of 15 μm. The coagulation bath is an anhydrous ethanol solution with a concentration of 73 wt%.
[0056] Comparative Example 6: A highly transparent, high-haze wood-based cellulose nanoparticle / polylactic acid composite film, the preparation method of which includes the following steps: S1. First, place PLA and LCNF in a desiccator and dry them at 40°C for 24 hours, then set aside for use. S2. Take 0.005 g of oven-dry LCNF (lignin content of 1.3 wt%) and add it to 50 g of N,N-dimethylacetamide (DMA) solution. Homogenize at 90 MPa pressure for 20 s to make LCNF uniformly dispersed in DMA and obtain a uniformly dispersed LCNF solution. S3. Weigh 1.5g of dried PLA and add it to the LCNF solution. Then place it in an oil bath at 80℃ and stir magnetically for 1 hour until it is completely dissolved to obtain an LCNF / PLA mixed solution. The mass fraction of PLA is 3% (mass fraction of PLA and DMA solution). S4. Pour 15 mL of LCNF / PLA mixed solution into a polytetrafluoroethylene petri dish, then place it in an electric heating drying oven and dry it at 90℃ for 40 min. Peel off the film to obtain the LCNF / PLA composite film.
[0057] Performance testing Nanofiber membranes were prepared according to the methods in the examples and comparative examples, and their performance was tested according to the following methods. The test results are recorded in Table 1.
[0058] 1. Transmittance: The transmittance of the membrane material was tested using a UV-Vis spectrophotometer, and the transmittance at a wavelength of 550 nm was taken as the characterization value of the transmittance of the membrane material.
[0059] 2. Breaking strength and elongation at break: Tensile tests were conducted using a METS E44.204 microcomputer-controlled electronic universal testing machine. The samples were prepared as 40mm × 10mm specimens. The tensile speed was 20mm / min. Ten sets of data were tested for each specimen. The clamp spacing was 10mm. The test temperature was 20℃ and the relative humidity was 65%. Breaking strength = F / ab, where F is the breaking strength (N), a is the specimen width (mm), and b is the specimen thickness (mm). Elongation at break = (L1 / L0-L1) × 100%, where LO is the original length of the specimen (mm) and L1 is the length at break (mm).
[0060] 3. The nanofiber membrane containing the nanocellulose / silk fibroin composite is placed outdoors, in contact with smog, with the other side facing indoors. Air circulation between the indoor and outdoor areas is solely through the nanofiber membrane. The removal efficiency (E%) is the ratio of the PM0.3 index at the indoor nanofiber membrane to the PM0.3 index at the outdoor filter membrane. The pressure difference (ΔP) is the pressure difference across the nanofiber membrane.
[0061] Table 1
[0062] As can be seen from Examples 1-3 and the data in Table 1, the nanofiber membranes prepared in Examples 1-3 have high light transmittance, reaching over 85%, and PM0.3 removal efficiency of over 80%, with a pressure difference of less than 100 MPa, exhibiting good air permeability.
[0063] In Examples 4 and 5, nanocellulose and silk fibroin were used in mass ratios of 4:6 and 6:4, respectively. It can be seen that in Example 6, the increased content of nanocellulose increased the tensile strength and elongation at break of the nanofiber membrane, but the light transmittance decreased. In Example 4, the increased amount of silk fibroin increased the light transmittance of the nanofiber membrane, but the mechanical strength weakened.
[0064] Compared with Example 1, Examples 6 and 7 also added bacterial cellulose to the PLA solution used for electrospinning. The light transmittance of the nanofiber membranes prepared in Examples 6 and 7 decreased, but the tensile strength and elongation at break increased, and the PM0.3 removal efficiency increased. The pressure difference across the nanofiber membrane decreased, and the air permeability was improved.
[0065] Compared with Example 6, Examples 8 and 9 show that the bacterial cellulose content in the PLA solution is reduced and increased, respectively. The nanofiber membrane prepared in Example 8 has higher transparency than that in Example 6, but its elongation at break and tensile strength are reduced, and the pressure difference is increased. In Example 9, the bacterial cellulose content is increased, the transparency of the nanofiber membrane is significantly reduced, the elongation at break and tensile strength are increased, and the pressure difference is further reduced. It has better air permeability and increased PM0.3 filtration effect. This indicates that the addition of bacterial cellulose can not only improve the mechanical strength of the nanofiber membrane, but also increase or decrease air permeability and filtration effect, but it will cause a decrease in the transparency of the nanofiber membrane.
[0066] Compared with Example 6, Examples 10 and 11 also used L-lactide, whey protein concentrate, etc. to pretreat bacterial cellulose. Table 1 shows that the transmittance of the nanofiber membranes prepared in Examples 10 and 11 did not change much, but the PM0.3 removal efficiency, pressure difference, elongation at break and tensile strength increased significantly. This indicates that pretreating bacterial cellulose can improve the mechanical strength and filtration efficiency of nanofiber membranes, but will have a slight impact on air permeability.
[0067] Compared with Example 10, Examples 12 and 13 did not use L-lactide and whey protein concentrate during the pretreatment of bacterial cellulose. The nanofiber membrane prepared in Example 12 showed a slight decrease in transparency, and its elongation at break and tensile strength were weakened, but the removal efficiency of PM0.3 was enhanced and the pressure difference was reduced. This indicates that L-lactide can reduce the porosity of bacterial cellulose and increase light transmittance and mechanical strength, but it will affect the air permeability and filtration effect to a certain extent. The nanofiber membrane prepared in Example 13 showed a slight increase in light transmittance, but the removal efficiency of PM0.3 decreased, indicating that whey protein concentrate can improve the filtration effect of the nanofiber membrane.
[0068] Compared with Example 10, the amounts of whey protein concentrate and bacterial cellulose grafts in Examples 14 and 15 changed. In Example 14, the amount of whey protein concentrate was reduced, while in Example 15, the amount of whey protein concentrate was increased. The transparency of the nanofiber membrane prepared in Example 14 increased, but the PM0.3 removal efficiency decreased. The transparency of the nanofiber membrane prepared in Example 15 decreased, but the PM0.3 removal effect increased.
[0069] Compared with Example 10, Examples 16 and 17 also involved pretreatment of the nanofiber cellulose / silk fibroin composite membrane. Table 1 shows that the PM0.3 removal efficiency and pressure difference of the nanofiber membranes prepared in Examples 16 and 17 were increased.
[0070] Compared with Example 16, Example 18 did not involve alkaline treatment of the nanocellulose / silk fibroin composite membrane. As can be seen, the PM0.3 removal efficiency, mechanical strength and light transmittance did not change much, but the pressure difference increased and the air permeability was weakened.
[0071] Compared with Example 1, Comparative Examples 1 and 2 increased and decreased the amount of nanocellulose added, respectively. In Comparative Example 1, the light transmittance decreased, and the elongation at break and tensile strength weakened, resulting in a poorer filtration effect. In Comparative Example 2, the nanocellulose content increased, the light transmittance decreased, and the filtration effect weakened, but the mechanical properties were slightly improved.
[0072] In Comparative Example 3, as the concentration of the mixed solution increased, the transparency of the nanofiber membrane decreased, its fracture resistance weakened, and the pressure difference increased.
[0073] In Comparative Example 4, no PET hexagonal mesh was cast into the nanofiber / silk fibroin composite membrane. Compared with Example 1, the light transmittance, mechanical strength, and PM0.3 removal efficiency of the nanofiber membrane prepared in Comparative Example 4 decreased, the pressure difference increased, and the air permeability weakened.
[0074] In Comparative Example 5, a nanofiber membrane made of nanocellulose / silk fibroin was used as the nanofiber membrane. Compared with Example 1, the transparency of the nanofiber membrane was increased, but the other properties were significantly reduced.
[0075] Comparative Example 6 is a nanofiber membrane containing nanocellulose and PLA prepared by existing technology. It has high transparency, but its removal efficiency for PM0.3 is poor, and the pressure difference during filtration is high, resulting in poor air permeability.
[0076] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for preparing a high-transparency nanofiber membrane, characterized in that, Includes the following steps: Nanocellulose and silk fibroin were mixed in a mass ratio of 4-6:4-6 and dissolved in a eutectic solvent to obtain a mixed solution with a concentration of 8-12 wt%. A PET hexagonal mesh is placed in a mold, the mixed solution is added to the mold, the film is poured and dried to obtain a semi-finished product, which is then soaked in a coagulation bath, peeled off, and air-dried to obtain a nanocellulose / silk fibroin composite film. Polylactic acid is dissolved to prepare a PLA solution with a concentration of 7-10 wt%. Using the nanocellulose / silk fibroin composite membrane as the receiving substrate, electrospinning is performed to form a PLA nanofiber membrane on the nanocellulose / silk fibroin composite membrane, thereby producing a highly transparent nanofiber membrane.
2. The method for preparing a high-transparency nanofiber membrane according to claim 1, characterized in that: The PLA solution also contains bacterial cellulose, and the mass ratio of bacterial cellulose to polylactic acid in the PLA solution is 0.3-0.45:
1.
3. The method for preparing a high-transparency nanofiber membrane according to claim 2, characterized in that: The bacterial cellulose undergoes the following pretreatment: Bacterial cellulose, L-lactide and stannous octoate were mixed, and dimethyl sulfoxide was added. The mixture was reacted at 130-140℃ for 9-10 hours to obtain bacterial cellulose grafts. Add whey protein concentrate to a 78-80 wt% acetic acid solution, stir at 75-80℃ to form a 1-1.5 wt% solution, add bacterial cellulose graft, mix and stir, and then dry.
4. The method for preparing a high-transparency nanofiber membrane according to claim 3, characterized in that: The mass ratio of whey protein concentrate to bacterial cellulose graft is 0.5-1:
2.
5. The method for preparing a high-transparency nanofiber membrane according to claim 1, characterized in that: The nanocellulose / silk fibroin composite membrane undergoes the following pretreatment: The nanocellulose / silk fibroin composite membrane was immersed in a 15-17% sodium hydroxide aqueous solution and allowed to stand for 10-12 hours. After washing with distilled water until neutral, it was dried and then immersed in an impregnation solution containing isopropanol, a 3.5-4 wt% sodium hydroxide aqueous solution, and a 45-50 wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution. The membrane was then immersed at 40-45℃ for 3-4 hours, washed with water, and dried.
6. The method for preparing a high-transparency nanofiber membrane according to claim 1, characterized in that: The PET hexagonal mesh has a side length of 1.5-2 mm.
7. The method for preparing a high-transparency nanofiber membrane according to claim 1, characterized in that: The thickness ratio of the nanocellulose / silk fibroin composite membrane to the PLA nanofiber membrane is 1:10-20.
8. The method for preparing the high-transparency nanofiber membrane according to claim 1, characterized in that: The eutectic solvent is a 5-8 wt% solution of 1,5-diazabicyclo[4.3.0]non-5-ene in acetylacetic acid.
9. The method for preparing a high-transparency nanofiber membrane according to claim 1, characterized in that: The coagulation bath is a 73-75 wt% aqueous ethanol solution.
10. A high-transparency nanofiber membrane, characterized in that, It is prepared using the method for preparing the high transparency nanofiber membrane according to any one of claims 1-9.
Citation Information
Patent Citations
Silk fibroin nanofiber membrane and preparation method thereof
CN103341209A
Silk fibroin composite film as well as preparation method and application thereof
CN109722039A
